Differential leukocyte counting and immunophenotyping in cryopreserved ex vivo whole blood. (16th December 2014) - Nemes, Elisa; Kagina, Benjamin M. N.; Smit, Erica; Africa, Hadn; Steyn, Marcia; Hanekom, Willem A.; Scriba, Thomas J.
Abstract Absolute cell counts are typically measured in fresh samples, but this is impractical in large field studies. We compared quantification of leukocyte proportions and absolute counts using reference real‐time methods (stain and lyse/no‐wash (LNW) or hematology analyser) with a novel assay that allows long‐term cryopreservation of fixed leukocytes for later counting (DLC‐ICE: differential leukocyte count and immunophenotype in cryopreserved ex vivo whole blood). For the LNW method, whole blood (WB) was stained with fluorescent antibodies, then erythrocytes were lysed, and leukocytes fixed prior to flow cytometry. Alternatively, our novel DLC‐ICE method entailed erythrocyte lysis and leukocyte fixation, cryopreservation and later staining of permeabilized cells prior to flow cytometry. Outcomes were proportions and absolute counts of granulocytes, lymphocytes, monocytes, T cells, B cells, and activated T cells within the leukocyte population. We also compared leukocyte subset counts in fresh WB from 51 healthy infants measured by hematology analyser at a rural clinical site or by DLC‐ICE method after 2 years of cryopreservation. We observed excellent agreement and strong correlations between absolute counts or cell proportions measured by the LNW and DLC‐ICE methods on fresh WB from 10 healthy adults. Compared to LNW, DLC‐ICE yielded similar or brighter staining even after cryopreservation. Duration of cryopreservation, assessed monthly for 1 year, had little effect on cell enumeration: median coefficients of variation were below 15% for all outcomes. Under field site conditions, we observed strong correlations between infant leukocyte numbers measured in fresh samples by hematology analyser and those measured by DLC‐ICE up to 2 years of cryopreservation. Our novel DLC‐ICE method allows accurate flow cytometric quantification of cell subsets from fixed WB even after long‐term cryopreservation. This method is ideal for batched, retrospective analysis of samples from large field studies, or when advanced flow cytometry equipment is not available for clinical research purposes. © 2014 International Society for Advancement of Cytometry